UTHM Total Campus Experience Application - MOHAMMAD HAZIQ BIN DASIM; MUNIRAH BINTI MOHD YUSOF (Applied Information Technology And Computer Science, 2022)
UTHM Total Campus Experience Application is an application that supports the smart campus function and helps students get information and guidance when they are on the UTHM campus. It is also an application that can help and guide new students about campuses, residential colleges and facilities related to students at UTHM. In addition, one of the modules in this application is intended to help students know their eligibility status to apply for appropriate assistance from the Office of Student Affairs (HEP) and UTHM Zakat Center such as Sabil al Hikmah, Zakat assistance, Death Benefit and so on. This makes it easier for students because if they already know whether they are eligible or not to receive the assistance, then they can apply manually through the HEP Office and UTHM Zakat Center. The development of this application is based on the Agile model. This Agile model was chosen because this model was developed in a short period of time that requires fast, rapid adaptation in the changes of an application. Among the activities in this Agile model are collecting requirements, designing requirements, developing applications, testing and deploying applications. The application is developed using Android Studio software and uses Java and XML programming languages. While the database is developed using Firebase available on Android Studio software. The app allows students to find out the situation of the shuttle bus, find out the results of assistance from HEP, get class notifications, guides for new students, news and notices about the campus. For administrators, administrators can update news, notices, class schedule displays and upcoming programs. Administrators can generate reports according to the selected month.